2007
DOI: 10.1001/archotol.133.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Bacterial Cells and Glycocalyx in Biofilms on Human Tonsils

Abstract: To demonstrate mucosal biofilms in human tissue by direct visualization of bacteria and glycocalyx using confocal laser scanning microscopy with double fluorescent staining on tonsils and to compare the findings with the results of scanning electron microscopy analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 36 publications
2
57
0
5
Order By: Relevance
“…11 In another study, the presence of biofilms on tonsils was shown using confocal scanning laser microscopy with double fluorescent staining, and 17 of 24 tonsils (71%) removed for chronic or recurrent tonsillitis contained biofilms. 12 In recent literature, articles have supported the hypothesis that COME pathogenesis may also be biofilm related. Presence of bacterial biofilms was shown in experimental otitis media induced in chinchillas by transbulbar injection of nontypable Haemophilus influenzae and in tympanostomy tubes removed from children with otorrhea.…”
Section: Grade 2 X2500mentioning
confidence: 95%
See 1 more Smart Citation
“…11 In another study, the presence of biofilms on tonsils was shown using confocal scanning laser microscopy with double fluorescent staining, and 17 of 24 tonsils (71%) removed for chronic or recurrent tonsillitis contained biofilms. 12 In recent literature, articles have supported the hypothesis that COME pathogenesis may also be biofilm related. Presence of bacterial biofilms was shown in experimental otitis media induced in chinchillas by transbulbar injection of nontypable Haemophilus influenzae and in tympanostomy tubes removed from children with otorrhea.…”
Section: Grade 2 X2500mentioning
confidence: 95%
“…10 Biofilm formation was also detected on adenoid and tonsil surfaces, particularly in children with recurrent infections. [11][12][13] The correlation between COME and biofilm formation was also studied with respect to resistance to medical treatment and the need for ventilation tube application. 14,15 The aim of this study was to investigate whether there was a relationship between adenoid surface biofilm formation and COME by using scanning electron microscopy (SEM).…”
mentioning
confidence: 99%
“…In chronic tonsillitis, anatomic evidence exists for the presence of both gram-positive and gram-negative bacterial biofilms [28]. Recently, bacterial biofilms have been detected in 70% of patients with chronic tonsillitis at the time of tonsillectomy [29]. Similarly, in a group of pediatric patients with CRS, adenoidectomy specimens revealed that nearly 95% of their surface was covered by mature bacterial biofilms.…”
Section: Adenotonsillar Diseasementioning
confidence: 99%
“…Biofilms have been detected in human tonsillar tissue. 44 46 Chole et al studied 15 tonsil specimens removed because of chronic infection, and also four removed because of chronic hypertrophy, as controls. 45 Eleven of the 15 specimens showed biofilm formation, but there were also small clusters of colonies present in the hypertrophied tonsils.…”
Section: Biofilmsmentioning
confidence: 99%